Microwave assisted synthesis of novel zinc(II) phthalocyanines bearing 1,3-diazido-2-propanoxy functional groups and investigation of their photochemical properties - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this study, three novel phthalonitriles (1, 2 and 3) bearing 1,3-diazido-2-propanoxy substituents were synthesized by conventional methods and their zinc(II) phthalocyanine complexes (4, 5 and 6) were synthesized by microwave irradiation because of the low stability of the azide groups at a high temperature under conventional heating. All novel compounds were fully characterized by elemental analyses, FT-IR, H-1 NMR, UV-Vis, and MALDI-TOF spectral data. Furthermore, spectroscopic and photochemical properties such as singlet oxygen generation and the photostability of these zinc(II) phthalocyanines were investigated in DMSO. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Zinc; Azide; Singlet oxygen; Microwave; PHOTOSENSITIZED SINGLET OXYGEN; BEHAVIOR; DESIGN